Mapping the Availability of Educational Facilities Using Geographic Information Systems in Each Study Program at the Faculty of Teacher Training and Education, Nusa Cendana University - Petronius Halatosa Asman; Arfita Rahmawati; Tugma Jaya Manalu (Journal Electrical and Computer Experiences, 2026)
The adequacy and spatial distribution of educational facilities are essential indicators of institutional readiness, particularly for study programs undergoing accreditation and quality assurance processes. However, facility planning in higher education is often conducted through administrative inventories without sufficient spatial evidence to identify location-based gaps. This study aims to map the availability and insufficiency of educational facilities across study programs at the Faculty of Teacher Training and Education (FKIP), Nusa Cendana University, using a Geographic Information System (GIS). A descriptive qualitative method with a spatial approach was employed. Primary data were collected through direct field observation and coordinate recording of study program locations using the GPS Map Camera application, while spatial processing and cartographic visualization were conducted using ArcMap 10.8. The findings indicate that most study programs have not fully met the facility standards required by the Independent Accreditation Agency for Education (LAMDIK), particularly in relation to scientific laboratories, microteaching laboratories, and library facilities. The GIS-based mapping provides accurate georeferenced information on study programs with facility deficiencies and visualizes their spatial distribution within the FKIP environment. This study contributes to evidence-based educational facility planning by demonstrating how GIS can support institutional decision-making, accreditation preparation, and the equitable distribution of educational infrastructure. The results are expected to serve as a practical basis for university leaders and faculty management in prioritizing facility improvement and aligning infrastructure development with accreditation standards.